THE IMPACT OF UKRAINE’S DIGITALIZATION IN WAR CONDITIONS ON STATE ADMINISTRATION IN SECURITY DIMENSIONS (Coordinates of Public Administration, 2026)
The article examines the transformation of Ukraine’s digital statehood in full-scale war conditions through the prism of international relations, public administration, and national security. It is proven that after February 24, 2022, digitalization ceased to be just a tool of administrative convenience and became a critical element of state capacity, institutional continuity, and security resilience. Based on the analysis of Ukrainian legislation, official government materials, EU documents, reports of international organizations, and professional academic literature, it is substantiated that the Ukrainian model of digital transformation in wartime is based on a combination of three functional contours: service, infrastructure-registration, and cybersecurity. The service circuit shows that the scaling of the Diya ecosystem and the launch of new military and recovery services – for IDPs, owners of damaged housing, veterans, families of military personnel, and citizens using international loss-fixing mechanisms – have reduced transaction costs, speeded up decisions, and increased the accessibility of the state in a crisis environment. The infrastructure and registry circuit reveals the crucial role of legislation on public electronic registries, cloud services, electronic identification, and trust services, as well as cloud migration of critical state data to data centers in the EU and the US, which reduced the risks of physical destruction, loss of accessibility, and destruction of state data due to kinetic strikes. The security circuit establishes that the Russian cyber campaign against Ukraine has evolved from predominantly destructive attacks in 2022 to more complex espionage, phishing, supply-chain, and multi-vector operations in 2023–2025; accordingly, cyber defense has been transformed into a multi-level system of cooperation between the state, the private sector, and international partners. The European integration dimension of digitalization is separately analyzed: Ukraine's association with the Digital Europe Programme, approximation to eIDAS and eIDAS 2.0, implementation of NIS/NIS2 approaches, development of the DT4UA and EU4DigitalUA projects, as well as the 2025 political decision to include Ukraine in the EU roaming area from 2026. It is substantiated that digitalization in wartime has become a form of strategic adaptation of public administration, and its further development should take place as a security policy, and not only as an administrative innovation. The article proves the need to transition from «digitalization of services» to «digital state capacity», where compatibility with the EU acquis, stability of telecom infrastructure, register integrity, cyber defense, inclusiveness, and data protection are interrelated components of one management project.